Induction of Robust Future Liver Remnant Hypertrophy Before Hepatectomy With a Modified Liver Venous Deprivation Technique Using a Trans-venous Access for Hepatic Vein Embolization - Degrauwe, Nils; Duran, Rafael; Melloul, Emmanuel; Halkic, Nermin; Demartines, Nicolas; Denys, Alban (Frontiers in Radiology, 2021)
Purpose Hepatic and/or portal vein embolization are performed before hepatectomy for patients with insufficient future liver remnant and usually achieved with a trans-hepatic approach. The aim of the present study is to describe a modified trans-venous liver venous deprivation technique (mLVD), avoiding the potential risks and limitations of a percutaneous approach to hepatic vein embolization. In addition, to assess safety, efficacy and surgical outcome after mLVD. Material and Methods Retrospective single-center institutional review board–approved study. From March 2016 to June 2019, consecutive oncologic patients with combined portal and hepatic vein embolization were included. CT volumetric analysis was performed before and after mLVD to assess liver hypertrophy. Complications related to mLVD and surgical outcome were obtained from medical records. Results Thirty patients (62.7 +/- 14.5 years old, 20 men), with liver metastasis (60%) or primary liver cancer (40%) underwent mLVD. Twenty-one patients (70%) had hepatic vein anatomic variants. Technical success of mLVD was 100%. Four patients had complications (3 minor, 1 major). FLR hypertrophy was 64.2 +/- 51.3% (mean +/- SD). Twenty-four patients (80%) underwent the planned hepatectomy and no surgery was cancelled as a consequence of mLVD complications or insufficient hypertrophy. Fifty percent of patients (12/24) had no or mild complications after surgery (Clavien-Dindo 0-II), and 45.8% (11/24) had more serious complications (Clavien-Dindo III-IV). Thirty-day mortality was 4.2% (1/24). Conclusion mLVD is an effective method to induce FLR hypertrophy. This technique is applicable in a wide range of oncologic situations and in patients with complex right liver vein anatomy.